Increased Bone Resorption: A Possible Pathophysiological Link Between Hypovitaminosis D and Peripheral Arterial Disease. Issue 3 (September 2016) - Pasqualini, L.; Ministrini, S.; Macura, A.; Marini, E.; Leli, C.; Siepi, D.; Lombardini, R.; Kararoudi, M.N.; Scarponi, A.M.; Schillaci, G.; Pirro, M.; Mannarino, E.
Abstract : Objective/Background: Vitamin D deficiency has been associated with the prevalence and severity of peripheral arterial disease (PAD); nevertheless, data on bone turnover in patients with PAD is lacking. The present study investigates a possible relationship between the markers of bone turnover and the presence and severity of PAD. Methods: The study examined 143 patients, with a mean ± SD age of 75.3 ± 8.5 years (range 50.0–93.0 years), of both sexes, admitted to a department of internal medicine. All patients underwent ankle brachial index (ABI) assessment by Doppler velocimetry. Serum levels of 25(OH) vitamin D and two markers of bone turnover, C-terminal telopeptide of type I collagen (sCTX) and bone isoenzyme of alkaline phosphatase, were measured. The differences between patients with normal ABI and patients with PAD were analyzed. Pearson and Spearman correlation coefficients were calculated and independent predictors were identified through a stepwise linear regression analysis. Odds ratios were calculated with a logistic regression model. Results: Compared with patients with a normal ABI (≥0.90), patients with PAD (ABI < 0.90) presented with significantly lower levels of 25(OH) vitamin D (12.2 ± 9.6 ng/mL vs. 16.7 ± 8.7 ng/mL; p  = .006) and a significantly higher concentration of sCTX (1.1 ± 0.7 ng/mL vs. 0.6 ± 0.4 ng/mL; p  < .001). There was a positive correlation between ABI and serum concentration of 25 (OH) vitamin D ( r  = 0.3; p  < .001), whereas ABI was inversely correlated with the concentration of sCTX ( r  = −0.358; p  < .001). At logistic regression analysis, age, cigarette smoking, and both vitamin D and sCTX were independent predictors of an ABI < 0.90. Conclusion: These results support the hypothesis that hypovitaminosis D and increased bone turnover are risk factors for the presence and severity of PAD. Furthermore, the presence of PAD, even if asymptomatic and diagnosed by a reduced ABI, could identify a population at risk for osteoporosis and osteomalacia.